2004
DOI: 10.3171/foc.2004.17.3.7
|View full text |Cite
|
Sign up to set email alerts
|

In vitro biomechanics of cervical disc arthroplasty with the ProDisc-C total disc implant

Abstract: An in vitro biomechanical study was conducted to compare the effects of disc arthroplasty and anterior cervical fusion on cervical spine biomechanics in a multilevel human cadaveric model. Three spine conditions were studied: harvested, single-level cervical disc arthroplasty, and single-level fusion. A programmable testing apparatus was used that replicated physiological flexion/extension, lateral bending, and axial rotation. Measurements included vertebral motion, applied load, and bending moments. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(76 citation statements)
references
References 28 publications
2
74
0
Order By: Relevance
“…1,10,16 With the option of arthroplasty, there is a theoretical assumption that reconstructing normal or near normal spinal biomechanics should diminish chances of further spinal degeneration and thus the development of ASD. 2,3,[6][7][8]11,15,18,19,21,23 Our study provides evidence supporting the hypothesis that arthroplasty may indeed be an alternative solution in a certain carefully selected cohort of ASD patients in whom conservative therapy has failed. Our results show that adequate decompression can be achieved along with improvement in the overall sagittal profile (as seen by an increase in cervical lordosis) due to an increase in the disc space angle and ROM at the treated level.…”
Section: Discussionsupporting
confidence: 69%
“…1,10,16 With the option of arthroplasty, there is a theoretical assumption that reconstructing normal or near normal spinal biomechanics should diminish chances of further spinal degeneration and thus the development of ASD. 2,3,[6][7][8]11,15,18,19,21,23 Our study provides evidence supporting the hypothesis that arthroplasty may indeed be an alternative solution in a certain carefully selected cohort of ASD patients in whom conservative therapy has failed. Our results show that adequate decompression can be achieved along with improvement in the overall sagittal profile (as seen by an increase in cervical lordosis) due to an increase in the disc space angle and ROM at the treated level.…”
Section: Discussionsupporting
confidence: 69%
“…Despite the promising accumulating clinical experience with disk replacements of varying designs, little work has been done to characterize the in vitro biomechanical features of varying replacements. DiAngelo et al [11] provided a biomechanical analysis of the ProDisc-C and demonstrated maintenance of normal motion at the treated and adjacent levels in all conditions except extension when compared with intact spines. Dmitriev et al [12] showed that the PCM implant maintained normal ROM at the treated and adjacent segments as well as maintaining normal intradiscal pressure at adjacent segments, parameters that are both increased in a fusion construct.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the implant is engineered to have a low profile without protrusion from the disk space and is secured via one midline keel in the superior level and two laterally placed keels in the inferior level to avoid conflict when multiple levels are instrumented. Despite the promising early clinical results and obvious theoretical benefits, there is a paucity of in vitro biomechanical data characterizing cervical arthroplasty devices in the literature [11,12,22]. In this study, we detail the kinematics of the entire subaxial cervical spine from C2 to C7 with the middle segment intact, treated by fusion, or replaced with an artificial disc implant.…”
Section: Introductionmentioning
confidence: 99%
“…The development of adjacent segment degeneration (ASD) following anterior cervical decompression and fusion (ACDF) is well reported in the literature [4][5][6][7][8][9][10][11][12][13][14][15]. Within the past few decades, both in vivo and in vitro biomechanical evidence suggest that arthrodesis may augment stress on the unfused adjacent levels [16][17][18][19][20][21]. Hilibrand et al [7] reported an annualized incidence of 2.9 % per year for developing symptomatic ASD after singlelevel ACDF and estimated that about 25.6 % of patients would have symptomatic ASD within 10 years of their index surgery.…”
Section: Introductionmentioning
confidence: 99%